Ultra-high precision x-ray polarimetry with artificial diamond channel cuts at the beam divergence limit - Bernhardt, Hendrik; Schmitt, Annika T.; Grabiger, Benjamin; Marx-Glowna, Berit; Loetzsch, Robert; Wille, Hans-Christian; Bessas, Dimitrios; Chumakov, Aleksandr; Rueffer, Rudolf; Roehlsberger, Ralf; Stoehlker, Thomas; Uschmann, Ingo; et al. (Physical Review Research, 2020)
We report on the use of synthetic single-crystal diamonds for high definition x-ray polarimetry. The diamonds are precision mounted to form artificial channel-cut crystals (ACCs). Each ACC supports four consecutive reflections with a scattering angle 2ΘB of 90∘. We achieved a polarization purity of 3.0×10-10 at beamline ID18 of the European Synchrotron Radiation Facility (ESRF). When the x-ray beam's horizontal divergence was reduced through additional collimation from 17 to 8.4μrad, the polarization purity improved to 1.4×10-10. Precision x-ray polarimetry thus has reached the limit, where the purity is determined by the divergence of the beam. In particular, this result is important for polarimetry at fourth generation x-ray sources, which provide diffraction-limited x-ray beams. The sensitivity expected as a consequence of the present work will pave the way for exploring new physics such as the investigation of vacuum birefringence.
CRIS-Team Scopus Importer:2023-04-20